2018
DOI: 10.1002/jeab.322
|View full text |Cite
|
Sign up to set email alerts
|

Formation of new stimulus equivalence classes by exclusion

Abstract: This study presents three experiments that aimed to show the formation of stimulus equivalence relations among stimuli that had been previously related only by exclusion. In Experiment 1, participants were trained on baseline conditional discriminations to establish two 3-member equivalence classes. Then, they were exposed to exclusion trials, without feedback, in which undefined stimuli had to be matched by rejecting the defined baseline stimuli. Finally, participants responded to test trials evaluating the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…One alternative explanation for responding to D and E stimuli on the transitivity‐like trials is that responses were based on exclusion. Exclusion consists of the conditional selection of a novel comparison stimulus that was not part of the conditional relations established in the baseline training (e.g., McIlvane, Kledaras, Lowry & Stoddard, ; McIlvane et al, ; Plazas & Cortes, ; Plazas & Villamil, ; Wilkinson, Dube, & McIlvane, ; Wilkinson & McIlvane, ). Insofar as the D and E stimuli were not part of the relations involved in the baseline training, responses to them on transitivity‐like trials could have been mediated by exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…One alternative explanation for responding to D and E stimuli on the transitivity‐like trials is that responses were based on exclusion. Exclusion consists of the conditional selection of a novel comparison stimulus that was not part of the conditional relations established in the baseline training (e.g., McIlvane, Kledaras, Lowry & Stoddard, ; McIlvane et al, ; Plazas & Cortes, ; Plazas & Villamil, ; Wilkinson, Dube, & McIlvane, ; Wilkinson & McIlvane, ). Insofar as the D and E stimuli were not part of the relations involved in the baseline training, responses to them on transitivity‐like trials could have been mediated by exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that control by exclusion can reverse the membership of preexisting classes (Meehan, 1995), and that stimuli related by exclusion might display properties in accordance with the equivalence relations (Lipkens, Hayes, & Hayes, 1993, Exp. 4;Wilkinson et al, 2009), and can be integrated to preexistent classes (Kastak & Schusterman, 2002), or extend the number of existent classes (Plazas & Villamil, 2017). In the latter study, it was found that exclusion responding could account for correct responses in transitivity test trials among stimuli that were not related among them by explicit training but they did by exclusion.…”
mentioning
confidence: 80%
“…In the study of Plazas and Villamil (2017), adult human participants learned the conditional discriminations required for the establishment of two three-member classes (A1B1C1 and A2B2C2). Then they were exposed to some exclusion trials employing as defined stimuli those related in the baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But science does not stagnate. The Equivalence Relations, Relational Frames, Acceptance and Commitment literatures have advanced understanding and application far beyond 1957 to grapple with issues from prejudice to psychotherapy and beyond (Arntzen, Granmo, & Fields, 2017;Avellaneda et al, 2016;Ayres-Pereira, Canovas, Varella, & de Souza, 2018;Beurms, Traets, De Houwer, & Beckers, 2017;Bordieri, Kellum, Wilson, & Whiteman, 2016;Carp & Petursdottir, 2015;Dixon, Enoch, & Belisle, 2017;Eilifsen & Arntzen, 2017;Fox & Kyonka, 2017;Griffith, Ramos, Hill, & Miguel, 2018;Guinther, 2017;Jennings & Miguel, 2017;López-López & Luciano, 2017;Ma, Miguel, & Jennings, 2016;Maraccini, Houmanfar, & Szarko, 2016;May, Stewart, Baez, Freegard, & Dymond, 2017;Mensah & Arntzen, 2017;Mizael, de Almeida, Silveira, & de Rose, 2016;Plazas & Villamil, 2018;Rippy & Doughty, 2017;Silveira et al, 2016). Regardless of whether this work is labeled as Equivalence Relations, Relational Frames, or Acceptance and Commitment, the similarities outnumber the differences and we hope this special section paves the way for consilience between these diverse and vital research programs.…”
Section: In This Issuementioning
confidence: 96%